The Proton-Sensing GPR4 Receptor Regulates Paracellular Gap Formation and Permeability of Vascular Endothelial Cells - Elizabeth A. Krewson; Edward J. Sanderlin; Mona A. Marie; Shayan Nik Akhtar; Juraj Velcicky; Pius Loetscher; Li V. Yang (iScience, 2020)
Summary: GPR4 is a pH-sensing G protein-coupled receptor highly expressed in vascular endothelial cells and can be activated by protons in the inflamed tissue microenvironment. Herein, we report that acidosis-induced GPR4 activation increases paracellular gap formation and permeability of vascular endothelial cells through the Gα12/13/Rho GTPase signaling pathway. Evaluation of GPR4 in the inflammatory response using the acute hindlimb ischemia-reperfusion mouse model revealed that GPR4 mediates tissue edema, inflammatory exudate formation, endothelial adhesion molecule expression, and leukocyte infiltration in the inflamed tissue. Genetic knockout and pharmacologic inhibition of GPR4 alleviate tissue inflammation. These results suggest GPR4 is a pro-inflammatory receptor and could be targeted for therapeutic intervention. : Pathophysiology; Molecular Mechanism of Behavior; Specialized Functions of Cells Subject Areas: Pathophysiology, Molecular Mechanism of Behavior, Specialized Functions of Cells